MdaB from Escherichia coli: cloning, purification, crystallization and preliminary X-ray analysis - Adams, Melanie A. (International Union of Crystallography, 2005)
The gene mdaB from Escherichia coli encodes an enzyme with activity similar to that of mammalian DT-diaphorase. It has been reported that the protein is able to confer resistance to the antibiotics DMP 840, adriamycin and etoposide. The gene was cloned and overexpressed in E. coli, allowing purification of the protein to homogeneity. The protein co-purified with an unidentified flavin. Suitable crystals for X-ray diffraction experiments were obtained by hanging-drop vapour diffusion. Their space group was triclinic P1, with unit-cell parameters a = 48.664, b = 52.099, c = 86.584 Å, α = 87.106, β = 86.889, γ = 63.526°. X-ray diffraction data were collected to 2.5 Å.